The question of ritual: a cognitive approach - Jesper Sørensen (Scripta Instituti Donneriani Aboensis, 2003)
Why does ritual continue to be an issue in religious studies and in anthropology? In this paper the author proposes a cognitive approach to rituals, focusing those aspects of rituals that are distinct from other types of actions, together with what cognitive responses these differences provoke. It will be argued that rituals violate basic causal assumptions and by doing so, trigger off cognitive processes in order to ascribe purpose and meaning to the action. In conclusion, this will be related to findings in ethology and evolutionary theory, arguing that ritual as a behavioural category plays an important role in the formation of symbolic thinking.